2021
DOI: 10.1111/are.15382
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different microalgae as monospecific and bispecific diets in larval rearing of Penaeus indicus with special reference to growth, nutrient composition and antimicrobial activity of microalgae

Abstract: To evaluate the efficiency of different microalgae in larval rearing of Indian white shrimp, Penaeus indicus, three different microalgae: Tetraselmis sp., Chaetoceros gracilis and Thalassiosira weissflogii were fed to the shrimp larvae either individually or in combination of two (1:1). The experiment showed that the survival, growth and stage conversion rate were significantly (p <  0.05) higher in combination of T. weissflogii: Tetraselmis sp. followed by T. weissflogii: C. gracilis. Further, significantly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…(Ekasari et al, to regulate the aquaculture water environment is currently one of the most effective ways to optimize the aquaculture water environment and increase shrimp production based on improving the survival rate of shrimp. (Marquez et al, 2019;Sandeep et al, 2021;Sandeep et al, 2023) At present, numerous scholars have con rmed the impact of microalgae regulation.For example, Chen et al discovered that the inclusion of microalgae effectively maintains pH stability and reduces ammonia nitrogen and nitrite levels in aquaculture ponds.(C. Huang et al, 2022a) Additionally, in their experiments, Julie Ekasari et al demonstrated that supplementing aquaculture water with microalgae not only stimulates the growth of Rottweiler shrimp but also provides a signi cant amount of essential fatty acids for their development.…”
Section: Introductionmentioning
confidence: 99%
“…(Ekasari et al, to regulate the aquaculture water environment is currently one of the most effective ways to optimize the aquaculture water environment and increase shrimp production based on improving the survival rate of shrimp. (Marquez et al, 2019;Sandeep et al, 2021;Sandeep et al, 2023) At present, numerous scholars have con rmed the impact of microalgae regulation.For example, Chen et al discovered that the inclusion of microalgae effectively maintains pH stability and reduces ammonia nitrogen and nitrite levels in aquaculture ponds.(C. Huang et al, 2022a) Additionally, in their experiments, Julie Ekasari et al demonstrated that supplementing aquaculture water with microalgae not only stimulates the growth of Rottweiler shrimp but also provides a signi cant amount of essential fatty acids for their development.…”
Section: Introductionmentioning
confidence: 99%
“…Marine diatoms such as the genus Chaetoceros, Thalassiosira exhibited the highest EPA and DHA fatty acid contents ranging from 11 to 19% of the total fatty acids (Volkman et al, 1989). Thalassiosira weissflogii has been known to improve the nutrient profile as well as the fatty acid composition when used as a live feed to shrimp larvae and copepod (Arendt et al, 2005;Kiatmetha et al, 2011;Sandeep et al, 2021). The use of T. weissflogii as a feed additive to cultured shrimp in pond improved the growth and also increased the fatty acid and astaxanthin contents of shrimp tail muscles (Ju et al, 2009).…”
Section: Introductionmentioning
confidence: 99%